2016
DOI: 10.1088/1367-2630/aa5116
|View full text |Cite
|
Sign up to set email alerts
|

Competition of edge effects on the electronic properties and excitonic effects in short graphene nanoribbons

Abstract: We explore the electronic properties and exciton effects in short graphene nanoribbons (SGNRs), which have two armchair edges and two zigzag edges. Our results show that both of these two types of edges have profound effects on the electronic properties and exciton effects. Both the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) states are alternatively changed between the bulk and the edge states as the lengths of the zigzag edges increase, due to the competition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…We set the on-site repulsion parameter to U = 8.29 eV for all calculations 38 . While some researchers [33][34][35]37 have used heavily screened values for U, we base our choice of this parameter on recent calculations of the Coulomb repulsion parameter in graphene 38,52,53 . The parameters we use in this article have been shown to result in a semi-metal solution for the ground state of graphene-like systems [54][55][56] , and are also similar to values used in calculations for other organic systems 49 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We set the on-site repulsion parameter to U = 8.29 eV for all calculations 38 . While some researchers [33][34][35]37 have used heavily screened values for U, we base our choice of this parameter on recent calculations of the Coulomb repulsion parameter in graphene 38,52,53 . The parameters we use in this article have been shown to result in a semi-metal solution for the ground state of graphene-like systems [54][55][56] , and are also similar to values used in calculations for other organic systems 49 .…”
Section: Methodsmentioning
confidence: 99%
“…While the optical properties of graphene have been extensively studied [18][19][20][21][22] including some finite size [23][24][25] and impurity [26][27][28] effects , the optical properties of finite size graphene flakes have not been, partly due to the shortcomings of mean field theory in finite systems. Previous studies 11,[29][30][31][32][33][34][35][36][37] have demonstrated that the size, shape, and the nature of the edges have an impact on the optical properties of these GFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, graphene nanoribbons (GNRs) are of special interest since they can be synthesized with atomic precision [4][5][6][7][8][9][10][11]. The development of synthesis processes and theoretical studies [12][13][14][15] have opened new research directions where the electronic properties of GNRs can be tuned and engineered by structuring the GNRs. For instance, heterojunctions of different types of GNRs or chevron-types GNRs have prompted much interest in this field [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Armchair GNRs (AGNRs) are often categorized into three families, based on their specific electronic band-gap versus width dependence [12][13][14]22] and defined by N a = 3p, 3p + 1, or 3p + 2 where N a is the number of atoms across the width of the unit cells (UCs) and p is an integer. However, tightbinding (TB) and k • p approximations predict a zero bandgap (i.e.…”
Section: Introductionmentioning
confidence: 99%